An Investigation of Doctoral Students’ Publication Experiences in a ‘Publish or No Degree’ Context - Shamsi, Ahmad Fawzi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2022)
The number of publications as research outputs has ever since become a critical factor in individuals’ and institutions’ performance measures as well as ranking the universities, leading to the flourish of an extensive number of journals publishing several issues annually. The blooming of publication has made many universities worldwide adopt the ‘publish or no degree’ policy in their doctoral programs, in which the PhD students are demanded to publish one article or more as a requirement for graduation. In spite of its importance in preparing doctoral students as researchers, the ‘publish or no degree’ policy has been reported in several studies as an additional source of ‘pains’ for the doctoral students in their highly challenging endeavor. To this end, the present study aims to investigate the perceptions of stakeholders about the ‘publish or no degree’ policy as a requirement for doctoral students’ graduation, then the challenges encountered by the doctoral students in writing for publication process, and finally the support they receive and/or need in writing for publication process in the context of an EMI (English as a medıum of instruction) university in North Cyprus. The study adopted a sequential mixed method in which the data was triangulated from different participants using different research toolsData analysis indicated that all participants were in favor of the ‘publication condition’ for graduation. However, this condition created a number of challenges faced by the doctoral students: article-related and non-article-related challenges. Article-related challenges were mainly linguistic and genre-related challenges. Although some doctoral students admitted that they received sufficient support throughout their Ph.D. study including the article-writing period, many participants emphasized a shortage in the support provided by their supervisors, faculty, and the university. Furthermore, the findings revealed that there is an urgent need for further support to enhance their publication literacy, such as creating research groups among the doctoral students, and immersing publication in the taught courses. It was also highlighted strongly that making changes in the university’s by-laws by expanding the number of acceptable indexes would open more publication channels and thus the waiting for publication status would be shortened.

ÖZ: Bilimsel araştırma ürünleri olan akademik yayınlar, bireylerin ve kurumların performans değerlendirmelerinde ve üniversitelerin sıralamasında önemli bir etken haline gelmiştir. Dünyada bilinen belli başlı birçok üniversitenin doktora programlarındaki öğrencilerden mezuniyet şartı olarak bir veya daha fazla makale yayınlamalarının talep edildiği ‘yayın yoksa mezuniyet de yok’ politikası sayesinde, hem akademik dergilerin hem de o dergilerde yer alan yayınların sayısında önemli bir artış olmuştur. Yayın koşulunun bir yandan doktora öğrencilerini araştırmacı rollerine hazırlamada gerçekten önemli bir etkiye sahipken, aynı zamanda doktora öğrencileri için zorlu, zaman zaman da acı verici bir deneyime dönüştüğü pek çok çalışmada rapor edilmiştir. Bu çalışma Kuzey Kıbrıs’ta yer alan ve eğitim dili İngilizce olan bir üniversitede doktora programı öğrencilerinin, tez danışmanlarının ve üniversitenin üst düzey yöneticilerinin, doktora programından mezun olabilmek için yayın koşulu politikasına nasıl baktıkları, yayın yapma sürecinde doktora öğrencilerinin yüz yüze kaldıkları ve zorlandıkları konuların neler olduğu ve makale yayınını gerçekleştirme sürecinde kimden nasıl destek aldıkları konusundaki düşünce, görüş ve önerilerini irdelemeyi amaçlamaktadır. ‘Sıralı karma araştırma’ yönteminin benimsendiği bu çalışmada, veri üçgenlemesini sağlamak amacıyla, farklı katılımcılar ve farklı veri toplama araçları kullanılmıştır. Elde edilen verinin analizi, tüm katılımcıların üniversitenin uyguladığı ‘doktora programından mezun olmak için makale yayınlama’ koşulunu desteklediklerini göstermiştir. Bununla birlikte, bu durumun doktora öğrencileri için ‘makale ile ilgili zorluklar ve makale ile ilgili olmayan zorluklar’ diye sınıflandırılabilecek bir dizi zorluk oluşturduğu ortaya konmuştur. Aldıkları ya da gereksinim duydukları destek konusunda ise, bazı doktora öğrencileri makale yazma dönemini de içeren doktora çalışmaları boyunca yeterli destek aldıklarını kabul etseler de, birçok doktora öğrencisi gerek tez danışmanları, gerekse diğer öğretim üyeleri ve üniversite tarafından sağlanan desteğin yetersizliğini vurgulamıştır. Yayın yapma pratiğini geliştirmek için doktora öğrencileri arasında araştırma grupları oluşturmak ve doktora programındaki derslerde öğrencilerin yayın yapma deneyimlerini artıracak çalışmalarda bulunmak gibi desteklere acil ihtiyaç olduğu ortaya konmuştur. Ayrıca, üniversite mevzuatında belirtilen mevcut endekslere ek olarak yeni endekslerin eklenmesinin, yayın bekleme süresini kısaltacak önemli bir katkı olacağı vurgulanmıştır.
Doctor of Philosophy in English Language Teaching (ELT). Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Education, Dept. of Foreign Language Education, 2022. Supervisor: Prof. Dr. Ülker Vancı Osam
Keywords: Thesis Tez